Truth in visual media : aesthetics, ethics and politics - La Caze, Marguerite; Nannicelli, Ted (Edinburgh University Press, 2021)
Shows how aesthetic, ethical, and political questions intersect in a range of art forms as found in traditional media.
Keywords: Truth in mass media.; Mass media -- Moral and ethical aspects.; Art -- Moral and ethical aspects.; Art -- Political aspects.; Truth.; Imagery (Psychology); Imagery (Psychology) -- In mass media.; Imagery, Psychotherapy.; Médias -- Aspect moral.; Art -- Aspect moral.; Art -- Aspect politique.; Vérité.; Imagerie (Psychologie); Imagerie (Psychologie) -- Dans les médias.; political art.; truth.; imagery.; Art -- Moral and ethical aspects; Art -- Political aspects; Mass media -- Moral and ethical aspects; Truth